Molecular Design of Encapsulin Protein Nanoparticles to Display Rotavirus Antigens for Enhancing Immunogenicity - Hyun-Gyo Jung; Seonghun Jeong; Min-Ji Kang; Ingi Hong; Young-Shin Park; Eunbyeol Ko; Jae-Ouk Kim; Deog-Young Choi (Vaccines, 2024)
Rotavirus considerably threatens global health, particularly for children <5 years. Current, licensed oral attenuated vaccine formulations have limitations including insufficient efficacy in children in low- and middle-income countries, warranting urgent development of novel vaccines with improved efficacy and safety profiles. Herein, we present a novel approach utilizing an encapsulin (ENC) nanoparticle (NP)-based non-replicating rotavirus vaccine. ENC, originating from bacteria, offers a self-assembling scaffold that displays rotavirus VP8* antigens on its surface. To enhance the correct folding and soluble expression of monomeric antigens and their subsequent assembly into NP, we adopted an RNA-interacting domain (RID) of mammalian transfer RNA synthetase as an expression tag fused to the N-terminus of the ENC-VP8* fusion protein. Using the RID-ENC-VP8* tripartite modular design, insertion of linkers of appropriate length and sequence and the universal T cell epitope P2 remarkably improved the production yield and immunogenicity. Cleavage of the RID rendered a homogenous assembly of ENC-P2-VP8* into protein NPs. Immunization with ENC-P2-VP8* induced markedly higher levels of VP8*-specific antibodies and virus neutralization titers in mice than those induced by P2-VP8* without ENC. Altogether, these results highlight the potential of the designed ENC NP-based rotavirus vaccine as an effective strategy against rotavirus disease to address global health challenges.